Side-Weir flow in curved channels - Agaccioglu, H; Yuksel, Y (ASCE-AMER SOC CIVIL ENGINEERS, 1998)
Side-weirs located on straight channels have attracted considerable interest and research effort. The same, however, is not true for side-weirs on curved channels. The existing studies deal mainly with sediment transport problems and lateral intake structures. The present study focuses on the investigation of the hydraulic behavior of a rectangular sharp crested weir at various locations along a 180 degrees bend. The flow resulting from the effects of the bend and the side-weir was investigated experimentally. Velocity measurements were carried out both for the bend with and without active overflow conditions while surface profiles were determined only for the former case. Velocity measurements were made over the depth at several cross sections along the bend. Observations indicated that a stagnation zone existed at the side-weir section along the inner side of the bend, and that standing waves were present downstream of the side-weir even under subcritical flow conditions. Both phenomena were found to be highly dependent on the upstream Froude number. The side-weir discharge coefficient was determined at one section along the approach to the bend and at five stations along the bend for a number of different side-weir dimensions. The side-weir discharge coefficient along the bend was found to depend on the upstream Froude number, the dimensionless weir height, p/h(1), and the dimensionless weir length, L/b. The variation of the discharge coefficient along the bend as a function of the Froude number and the dimensionless weir length was found to exhibit a parabolic relationship.
Keywords: DISCHARGE COEFFICIENT; Agriculture; Engineering; Water Resources